PENGARUH PENAMBAHAN EKSTRAK JAHE (Zingiber Officinale) DAN ASAP CAIR (Liquid Smoke) DENGAN LAMA PENGASINAN TERHADAP KUALITAS KEDALAMAN RONGGA UDARA DAN LEMAK KUNING TELUR - Asmayani Asmayani; Effendi Abustam; Irmawaty Irmawaty (State Islamic University (UIN) Alauddin, 2014)
ABSTRACT. This study was conducted in October-November 2013. Located in laboraty of Integrated Animal Production Techonology Faculty of Science and Technology Alauddin State Islamic University of Makassar. This study aimed to determine the effect of ginger extract and liquid smoke and the length of marinated salted egg on the quality of salted egg. The research method was based on the completely randomized design (CRD) with the general pattern 5 x 3 with 3 replications the treatments were: Factor A, The concentration of 1. ginger extract (0 %) + liquid smoke (0 %), 2. ginger extract (0 %) + liquid smoke (10 %), 3. ginger extract (10 %) + liquid smoke (0 %), 4. ginger extract (0 %) + liquid smoke (20 %), 5. ginger extract (20 %) + liquid smoke (0 %). Factor B, Period of marinated salted egg, 1. (6 days), 2. (8 days), 3. (10 days). Data was analyzed by analysis of variance using a completely Randomized Rancanagan (CRD) based the of consistend, 8 parameters of egg quality tested using the Least Significant Difference Test (BNT). Based on the analysis of variance showed that the addition of ginger extract (Zingiber Officinale) and liquid smoke (Liquid Smoke) can affect the value of the depth of the air cavity (P<0,05) and the value of fat (P<0,01).